2019
DOI: 10.4269/ajtmh.18-1009
|View full text |Cite
|
Sign up to set email alerts
|

Making Pastoralists Count: Geospatial Methods for the Health Surveillance of Nomadic Populations

Abstract: . Nomadic pastoralists are among the world’s hardest-to-reach and least served populations. Pastoralist communities are difficult to capture in household surveys because of factors including their high degree of mobility over remote terrain, fluid domestic arrangements, and cultural barriers. Most surveys use census-based sampling frames which do not accurately capture the demographic and health parameters of nomadic populations. As a result, pastoralists are “invisible” in population data such as t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…This challenge led at least one study in our sample to conduct an independent census of the study area prior to their immunisation campaign, which found that only 2.6% of children were current with their immunisation status [51]. Delivery innovations that leverage geospatial analysis and mobile phones have demonstrated promise in improving demographic surveillance among mobile pastoralists, but significant progress remains to be made [2,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This challenge led at least one study in our sample to conduct an independent census of the study area prior to their immunisation campaign, which found that only 2.6% of children were current with their immunisation status [51]. Delivery innovations that leverage geospatial analysis and mobile phones have demonstrated promise in improving demographic surveillance among mobile pastoralists, but significant progress remains to be made [2,55].…”
Section: Discussionmentioning
confidence: 99%
“…Pastoralist populations practise animal husbandry as their primary economic activity and typically practise some degree of mobility, defined in this paper as any type of seasonal transhumance carried out while managing livestock. Systematic underrepresentation in population data further hinders efforts to include pastoralists in health services planning, and demographic information is so incomplete that not even their population is known [1,2]. Estimates are outdated and range from 50 to over 200 million individuals globally, while the African Union estimates there are 268 million pastoralists on the African continent alone [3–5].…”
Section: Introductionmentioning
confidence: 99%
“…Five broad areas of research were identified among the included papers. The first area included epidemiologic studies that focused primarily on the prevalence of, and biomedical risk factors for, specific diseases or conditions, such as cholera, TB, and rabies (16). A second area comprised studies focused on the knowledge, attitudes and practices specific to certain conditions (e.g., pregnancy) and diseases (e.g., Rift Valley Fever) and the factors determining or correlating with knowledge, attitudes and practices (25).…”
Section: Research Areas and Study Objectivesmentioning
confidence: 99%
“…Specific human health topics. The health topic foci included reproductive health issues (including antenatal care, maternal mortality and/or childbirth) (21); vaccine-preventable disease/immunization topics (excluding polio) (14); general health service access, uptake or delivery (9); primary health care (4); or disease-specific topics such as tuberculosis (16), neglected tropical diseases (9), polio (9), malaria (8), HIV/AIDS (4) and zoonoses (3) (S2 Fig). Five papers on other unique topics were also reviewed (not listed individually).…”
Section: Research Areas and Study Objectivesmentioning
confidence: 99%
“…Including pastoralists in household surveys such as the DHS is an essential first step to guide health service planning. Satellite imagery has been used to conduct health assessments among sedentary populations and, more recently, to generate representative sampling frames for conducting health surveys among nomadic pastoralists directly comparable with the DHS over a large geographic scale [17, 18]. Such geospatial methods open up logistically and economically feasible alternatives to census listings and should be used to construct sampling frames capable of accounting for mobility.…”
Section: Roadmap: Potential Solutionsmentioning
confidence: 99%